Workshop On Teaching English Using The Communicative Approach For Teachers At The Elementary, Junior High, And High School Levels In Kiara Pandak Village - Pirman (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
Education provides an essential role in societal progress, and better teaching methods are required to pique students' interest in the learning process. This essay seeks to act as a type of community service on learning innovation by assisting students in Indonesia, particularly at Kiara Pandak Village School, in becoming more engaged in English courses through communicative approach methods. The communicative approach method is actively used in the classroom to require students to think critically, train their abilities, and be creative. This strategy can be applied to all subjects in school. Activities are organized to pique students' interest in learning English as a foreign language. Based on the results of the classroom assessment of effective learning methods, it is recommended that these strategies be used on a regular basis in English learning activities because they have been shown to boost students' interest and passion for learning. The article was produced based on the outcomes of workshop activities that assisted teachers in discovering the most successful and enjoyable style to teach English in Kiara Pandak Village, Bogor, West Java. Pendidikan memiliki peran penting dalam kemajuan masyarakat, dan metode pengajaran yang lebih baik diperlukan untuk menarik minat siswa dalam proses pembelajaran. Tulisan ini berusaha untuk bertindak sebagai bentuk pengabdian masyarakat dalam inovasi pembelajaran dengan membantu para siswa di Indonesia, khususnya di Sekolah Desa Kiara Pandak, untuk lebih terlibat dalam pelajaran bahasa Inggris melalui metode pendekatan komunikatif. Metode pendekatan komunikatif digunakan secara aktif di dalam kelas untuk menuntut siswa berpikir kritis, melatih kemampuan mereka, dan kreatif. Strategi ini dapat diterapkan pada semua mata pelajaran di sekolah. Kegiatan-kegiatan diselenggarakan untuk menarik minat siswa dalam mempelajari bahasa Inggris sebagai bahasa asing. Berdasarkan hasil penilaian kelas terhadap metode pembelajaran yang efektif, disarankan agar strategi ini digunakan secara teratur dalam kegiatan pembelajaran bahasa Inggris karena telah terbukti dapat meningkatkan minat dan semangat belajar siswa. Artikel ini dibuat berdasarkan hasil dari kegiatan lokakarya yang membantu para guru dalam menemukan cara yang paling berhasil dan menyenangkan untuk mengajar bahasa Inggris di Desa Kiara Pandak, Bogor, Jawa Barat.